밭전환 논에서 심토파쇄에 따른 사료용옥수수의 수량성 변화 - 서종호; Jong-ho Seo; 백성범; Sung-beom Back; 권영업; Young-up Kwon; 김충국; Chung-guk Kim; 정광호; Kwang-ho Jung; 정건호; Gun-ho Jung; et al. (Korean journal of crop science, 2012)
Low silage corn yield due to bad soil physical properties in the paddy field converted to upland condition is the chief obstacles to expanding the area for silage maize production. The effect of subsoiling (subsoiling to depth 40 cm) on soil physical properties and silage corn yield were investigated in the first year of paddy field converted to upland condition in 2010 and 2011, respectively. Soil compaction was loosened much particularly at depth 25∼35cm as much as 1∼1.5 MPa and soil bulk density and porosity at depth 15∼30 cm are improved by subsoiling. Maize growth was increased by subsoiling, particularly in kernel number per ear which increased ear weight. Total digestible nutrients (TDN) yield of silage maize was increased as much as 19 and 39% in 2010 and 2011, respectively showing that yield increase according to subsoiling was higher when maize growth was prohibited much by excess-moisture injury due to heavy rain in 2011.